Itinerários na coleção de gessos da Faculdade de Belas-Artes da Universidade de Lisboa - Duarte, Eduardo (2023)
The plaster collection of the former Academy of Fine Arts of Lisbon, today the Faculty of Fine Arts of the University of Lisbon currently has three essential aspects: a field of memory and history of the educational establishment itself; a repository of didactic material that students still use today to draw, paint or sculpt; and a field linked to conservation and restoration, in which the collection itself has been studied, recovered and conserved by the students of this faculty over the last decade. If the first aspect is fundamental, the second can be important and the last is essential, as a way of preserving and studying the collection. The plaster collection in its multiple polysemy can be understood as a landscape, in which itineraries, paths, and physical and mental journeys can be created; routes, departing but arriving unknown, which this article proposes to carry out